Feasibility of mini-sprinkler irrigation system in direct seeded rice (Oryza sativa) in Indo-Gangetic plains of India - SINGH, RANBIR; SINGH, AJAY; KUMAR, SATYENDRA; RAI, A K; RANI, SONIA; SHARMA, D K; JOSHI, P K; CHAUDHARI, S K; DEY, PARDIP; K, THIMMAPPA; TRIPATHI, R S (The Indian Journal of Agricultural Sciences, 2020)
Surface irrigation methods in puddle transplanted rice (PTR) requires a huge amount of irrigation water and leads to decline in water table in rice (Oryza sativa L.) growing areas of Indo-Gangetic Plains (IGP) of India. Mini sprinkler irrigation system with high water application efficiency in direct seeded rice (DSR) can save substantial amount of irrigation water. With this hypothesis, a four-year field experiment was conducted at ICAR-Central Soil Salinity Research Institute, Karnal to assess the feasibility of mini-sprinkler irrigation system for growing rice crop under conservation agriculture. Total 4 treatments, viz. mini-sprinkler irrigation system in direct seeded rice (SPRL-DSR), mini-sprinkler irrigation system in direct seeded rice with 1/3rd wheat residue (SPRL-DSR+R), surface irrigation in direct seeded rice (SUR-DSR), and surface irrigation in puddle transplanted rice (SUR-TPR), were laid out. Significantly higher grain yield, grains/panicle, and 1000-grain weight were recorded under SUR-TPR, while higher number of effective tillers/m.r.l. was recorded in SUR-DSR. The yield penalty in SPRL-DSR (6.84 t/ha) was 8.3% as compared to SUR-TPR. The saving in irrigation water and nitrogen was found to be 52.8 and 26.7%, respectively in SPRL-DSR as compared to SUR-TPR. SPRL-DSR also recorded 1.6-2.6 times higher grain water productivity (GWP) in comparison of SUR-TPR. Higher water and nitrogen use efficiency suggest that mini-sprinkler irrigation system is a viable option for DSR cultivation in groundwater depleting Indo-Gangetic plains of India.